2021
DOI: 10.3390/nursrep11020026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Initial Emotional States and Self-Efficacy Changes on Nursing Students’ Practical Skills Performance in Simulation-Based Education

Abstract: Training through simulation has shown to increase relevant and specific skills sets across a wide range of areas in nursing and related professions. Increasing skills has a reciprocal relation to the development of self-efficacy. A study was conducted to assess changes in the development of self-efficacy in simulation training for 2nd year nursing students. Initial emotional states, pre and post self-efficacy, and expert ratings of simulation performance were assessed. Results show that students who displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
0
9
0
2
Order By: Relevance
“…This is supported by several studies exploring the impact of clinical simulation on self‐efficacy beliefs amongst preregistration and novice nurses (Franklin & Lee, 2014; Pike & O’Donnell, 2010). A recent study showed that the effect of simulation on self‐efficacy could be influenced by students’ initial perception of mood, activation and control (Lugo et al, 2021). Moreover, students who lack feeling of control and self‐efficacy have been reported to experience higher stress levels and also lower learning outcomes (Leigh, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by several studies exploring the impact of clinical simulation on self‐efficacy beliefs amongst preregistration and novice nurses (Franklin & Lee, 2014; Pike & O’Donnell, 2010). A recent study showed that the effect of simulation on self‐efficacy could be influenced by students’ initial perception of mood, activation and control (Lugo et al, 2021). Moreover, students who lack feeling of control and self‐efficacy have been reported to experience higher stress levels and also lower learning outcomes (Leigh, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To measure students' perceived stress, self‐efficacy and control in relation to the simulation, as well as their evaluation of the proAct course, we utilized different questionnaires: The SelfAssessment Manikin for measuring emotion (SAM) (Bradley & Lang, 1994) was completed prior to and after the students' second simulation respectively (the nature of this spesific simulation varied between students). Here, we included four items from the SAM, which we assumed related to students' perception of stress and anxiety (Lugo et al, 2021), namely mood, activation, control and self‐efficacy. The SAM also includes an evaluation, where respondents are asked how secure they feel about their own assessments.…”
Section: Methodsmentioning
confidence: 99%
“…Self-efficacy (SE) has been identified as a factor that can influence nursing activities and nursing performance [ 11 , 12 ]. SE is therefore a fundamental aspect of the nursing profession, as it is closely linked to decisions taken in clinical nursing care [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, os cenários simulados que emulam situações clínicas em enfermagem, possibilitam a aquisição de habilidades técnicas e não técnicas (atitudes, trabalho interdisciplinar e comunicação), de forma direcionada, em um ambiente seguro e sem exposição do paciente. (ROSA et al, 2020;LUGO et al, 2021).…”
Section: Discussionunclassified
“…O desenvolvimento e validação de cenários possibilita ao estudante mobilizar conhecimentos prévios, estimula as habilidades metacognitivas como o pensamento e julgamento clínico. Isso refletirá na tomada de decisão acurada em situações assistenciais semelhantes (LUGO et al, 2021). Logo, avaliação e identificação de arritmias chocáveis em um cenário clínico tem o propósito de mobilizar habilidades para atuação segura e rápida em situações reais da prática profissional do enfermeiro.…”
Section: Discussionunclassified